2021
DOI: 10.1016/s0140-6736(20)32714-8
|View full text |Cite|
|
Sign up to set email alerts
|

First-line nivolumab plus ipilimumab in unresectable malignant pleural mesothelioma (CheckMate 743): a multicentre, randomised, open-label, phase 3 trial

Abstract: BACKGROUND: Approved systemic treatments for malignant pleural mesothelioma (MPM) were limited to chemotherapy regimens that have moderate survival benefit with poor outcomes. Nivolumab plus ipilimumab showed clinical benefit in other tumour types, including first-line non-small cell lung cancer. We hypothesised that this regimen would improve overall survival in MPM. METHODS:This open-label phase 3 study was conducted at 103 hospitals across 21 countries. Adults with previously untreated, histologically confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
652
2
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 808 publications
(781 citation statements)
references
References 27 publications
16
652
2
14
Order By: Relevance
“…Recently, the use of immune checkpoint inhibitor (ICI) as single agents or in combination in previously treated and naïve patients has been shown to potentially prolong MPM patient survival even if the value of single agent checkpoint inhibitors is rather limited yielding overall response rates with immunotherapy around 30% (31). Even if more recently the Checkmate-743 study demonstrated a significant improvement in overall survival for the combination of nivolumab and ipilimumab (32), some issues about the expected response and the acceptable toxicity need to be addressed. While the clinical efficacy of ICI has been claimed to correlate with a high tumor mutational burden as in melanoma or NSCLC patients, mesothelioma has consistently been demonstrated to harbor a low mutation burden (10).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of immune checkpoint inhibitor (ICI) as single agents or in combination in previously treated and naïve patients has been shown to potentially prolong MPM patient survival even if the value of single agent checkpoint inhibitors is rather limited yielding overall response rates with immunotherapy around 30% (31). Even if more recently the Checkmate-743 study demonstrated a significant improvement in overall survival for the combination of nivolumab and ipilimumab (32), some issues about the expected response and the acceptable toxicity need to be addressed. While the clinical efficacy of ICI has been claimed to correlate with a high tumor mutational burden as in melanoma or NSCLC patients, mesothelioma has consistently been demonstrated to harbor a low mutation burden (10).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Horn et al demonstrated improved immune response and prognostically favorable TME remodeling of breast and lung cancer in a murine model after simultaneous inhibition of the CXCR1/2 and TGF-ß pathway during PDL-1 therapy [112]. As PDL-1 treatment in combination with a cisplatin-pemetrexed based chemotherapy [4,113] has yielded relatively promising results in MPM therapy so far, and with us showing increased activation of the corresponding pathways, transferring this experimental approach to the MPM might be important for future multimodal treatment.…”
Section: Secretion Of Cytokines and Communication With The Immune Systemmentioning
confidence: 99%
“…This malignancy originates from the pleural mesothelium and is associated with a bad prognosis. Median survival times range from 14-20 months after initial diagnosis [3][4][5]. Generally, MPM can be differentiated into three major histologic subtypes, epithelioid (EMM), sarcomatoid (SMM), and biphasic (BMM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerically better results have been demonstrated with the combination of a PD-1/PD-L1 inhibitor with a cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) inhibitor (ORR of 25%, mPFS of 5.6-5.7 months, mOS of 16-16.6 months) (18,19). Recently, the combination of nivolumab, a PD-1-inhibitor, with ipilimumab, a CTLA-4 inhibitor, in treatment-naïve MPM, resulted in better OS as compared to therapy with platinum/pemetrexed (20). BRCA1 associated protein-1 (BAP1) is responsible for deubiquitination of histones and, as a result, protein transcription and cell cycle regulation (21), it also acts as a homologous recombination deoxyribonucleic acid (DNA) repair component found in the BRCA1/BARD1 complex (22).…”
Section: Introductionmentioning
confidence: 99%